Molecular characterisation of non-absorptive and absorptive enterocytes in human small intestine - Gaßler, Nikolaus; Newrzella, Dieter; Böhm, C.; Lyer, S.; Li, Li; Sorgenfrei, O.; Laer, L. van; Sido, Bernd; Mollenhauer, Jan; Poustka, Annemarie; Schirmacher, Peter; Gretz, Norbert (Gut, 2006)
Background and aims: Perturbation of differentiation of the crypt-villus axis of the human small intestine is associated with several intestinal disorders of clinical importance. At present, differentiation of small intestinal enterocytes in the crypt-villus axis is not well characterised. - Subjects and methods: Expression profiling of microdissected enterocytes lining the upper part of crypts or the middle of villi was performed using the Affymetrix X3P arrays and several methods for confirmation. - Results: A total of 978 differentially expressed sequences representing 778 unique UniGene IDs were found and categorised into four functional groups. In enterocytes lining the upper part of crypts, cell cycle promoting genes and transcription/translation related genes were predominantly expressed, whereas in enterocytes lining the middle of villi, high expression of cell cycle inhibiting genes, metabolism related genes, and vesicle/transport related genes was found. - Conclusion: Two types of enterocytes were dissected at the molecular level, the non-absorptive enterocyte located in the upper part of crypts and the absorptive enterocyte found in the middle of villi. These data improve our knowledge about the physiology of the crypt-villus architecture in human small intestine and provide new insights into pathophysiological phenomena, such as villus atrophy, which is clinically important.
Gesehen am 15.06.2022